2016
DOI: 10.1002/kin.21052
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Micelle Formation and Added Salts on the Hydrolysis Reaction Rate of p‐Nitrophenyl Benzoate in Aqueous Buffered Media

Abstract: The hydrolysis reaction rate of p-nitrophenyl benzoate (p-NPB) has been examined in aqueous buffer media of pH 9.18, containing surfactants, cetyltrimethylammonium bromide (CTAB) and chloride (CTAC), or sodium dodecyl sulfate (SDS) at 35°C. Although the rate constant [log (k/s −1 )] of p-NPB hydrolysis has once decreased slightly below the critical micelle concentration (CMC) value for CTAB and CTAC, it has begun to increase drastically with micellar formation. With increasing concentrations larger than the CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The pseudo‐first‐order rate constant increases in the presence of a small amount of surfactant above the critical micelle concentration (cmc) until it reaches a maximum; after this point, an increase in surfactant concentration diminishes the observed rate constant (see Figures ). This behavior is explained considering the micelle formation, the amount of substrate in the micelles, the competition between OH − , borate and the increasing amount of Br − , and the dilution of the substrate in the micelles …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The pseudo‐first‐order rate constant increases in the presence of a small amount of surfactant above the critical micelle concentration (cmc) until it reaches a maximum; after this point, an increase in surfactant concentration diminishes the observed rate constant (see Figures ). This behavior is explained considering the micelle formation, the amount of substrate in the micelles, the competition between OH − , borate and the increasing amount of Br − , and the dilution of the substrate in the micelles …”
Section: Resultsmentioning
confidence: 99%
“…This behavior is explained considering the micelle formation, the amount of substrate in the micelles, the Table S3 in the Supporting Information) and the curves were calculated with Equations 2 to 7 and values of Table 2. competition between OH − , borate and the increasing amount of Br − , and the dilution of the substrate in the micelles. [12] These studies have suggested strongly that in micellar media, most reactions take place on the surface of micelle at or near the highly charged double layer, commonly called the Stern layer.…”
Section: Hydrolysis Reactions Of Thionocarbonates and Carbonates Inmentioning
confidence: 99%
See 3 more Smart Citations